2001
DOI: 10.1016/s0735-1097(00)01039-1
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and early recurrence of atrial fibrillation after electrical cardioversion

Abstract: Two weeks later, 25 patients presented with AF. Spectral analysis of HRV revealed that patients wi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
2
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 31 publications
4
69
2
1
Order By: Relevance
“…31,32) Limitations: The limitations of this study are as follows. First, it was a retrospective observational investigation and therefore there was bias in the patient background factors.…”
Section: Discussionmentioning
confidence: 99%
“…31,32) Limitations: The limitations of this study are as follows. First, it was a retrospective observational investigation and therefore there was bias in the patient background factors.…”
Section: Discussionmentioning
confidence: 99%
“…Lombardi F et al showed that the LF/HF obtained from heart rate variability analyses 4 to 5 hours after electrical cardioversion was useful to predict the short-term recurrence of PAf, and insisted that autonomic activity was closely related to PAf recurrence around 2 weeks after cardioversion. 7) Puglisi A et al evaluated the suppressive effect of three kinds of pacemaker rate-responsive algorithms on PAf, including conventional response, overdrive pacing and CLS modes, and found that the CLS mode effectively suppressed PAf for 4 and 7 months after PMI. 6) They inferred that turbulent autonomic Figure 2 Memory data obtained from pacemaker Based on memory data obtained from pacemaker clinic, the rates of ventricular and atrial pacing and atrial sensing more rapid than 150 bpm as surrogate marker of atrial fibrillation are shown.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Of interest, even excessive slowing of the heart rate by intense VNS is not sufficient to initiate AF; however, the occurrence of spontaneous or induced atrial premature depolarization or burst pacing in the presence of VNS invariably initiates the arrhythmia. 5,6 There are reports in the basic literature 7,8 as well as in clinical reports 9,10 suggesting that vagal activation can be antiarrhythmic. Tai et al 9 reported that focal firing from the pulmonary veins (PVs) in patients with AF was suppressed by intravenous administration of phenylephrine, possibly through increased vagal tone caused by baroreflex activation.…”
mentioning
confidence: 99%